Parental attachment and cyberbullying among Malaysian children - Yusup, Sarina (2015)
This study examined the relationships between parental attachment towards children and cyberbullying (an online risky behavior) among Malaysian schoolchildren as moderated by gender. Specifically, this study was conducted with the aim of achieving five objectives namely i) to identify the patterns of Internet usage among Malaysian children;ii) to identify the level of parental attachment (i.e. communication, trust and alienation) between Malaysian children and parents; iii) to identify the level of cyberbullying experience among the children; iv) to determine the relationships between parental attachment (i.e. communication, trust and alienation) and cyberbullying among the children; and v) to test the moderating effects of gender on the relationships between parental attachment (i.e. communication, trust and alienation) and cyberbullying among Malaysian children. Despite the increase in the number of cyberbullying cases among children in Malaysia,few empirical studies had been conducted to investigate the effects of the phenomenon,especially on the relationships between cyberbullying and parental attachment. Some of those problems prompted this study. Therefore, the researcher designed a structured survey instrument and self-administered it to a sample of 375 schoolchildren and either one of their parents was selected using the stratified sampling method. The ages of the respondents ranged from 9 to 16 years old. Moreover, the schoolchildren’s age and school category formed the primary basis (criteria) for drawing the sample of both the subjects of and locations to conduct the study. This study was conducted in two pairs of primary and secondary schools at Sepang and Gombak districts in Selangor state. The data were analyzed using SPSS version 22 and SEM-Amos version 22 softwares. This study adopted the attachment theory perspectives, and it suggests that lack of emotional security by parents towards their children could negatively affect the children’s behavior. This implies that the affected children could become vulnerable to cyberbullying incidents. Thus, the dependent variable of the study was cyberbullying,and it was measured based on the two sub-scales of the (cyberbullying) variable using 10 items. The two sub-scales were online harassment and sexually based bullying. Furthermore, to evaluate the convergent validity of the perceptual measurements, Confirmatory Factor Analysis (CFA) tests were run using AMOS software. The values of regression coefficient (r = .60 to .83) and Goodness-of-fit (GOF) indices showed that each of the item in the cyberbullying construct were related to each other and measured the construct ideally. Meanwhile, the independent variables of the study consisted of parental attachment constructs, namely communication, trust and alienation (developed by Armsden and Greenberg, 1987), were hypothesized to have significant effects on cyberbullying incidents among the children. Importantly, this study integrated gender in the conceptual framework as a moderator variable because previous studies have suggested that a child’s gender plays significant roles in parent-child’s relationships, in this case cyberbullying. The outcomes of this study revealed that parents and children acknowledged that the frequency of Internet usage among the children was high. However, concerning the level of cyberbullying among the children, the results indicated that majority of them reported having never experienced cyberbullying. Moreover, the hypotheses of the study were tested using the Structural Equation Modeling (SEM) AMOS software and the results revealed that alienation of parental attachment (β = .231, p = .001) was more reliable predictor for cyberbullying than communication and trust of parental attachment were. In addition, values of the test of the moderating variable (β = .104, p = .009) confirmed the presence of moderating effects. Hence, the moderating path results indicated a strong presence of moderating effects by female gender on the relationships between alienation of parental attachment and cyberbullying. Whereas, the moderating effects were not detected in communication and trust of parental attachment constructs. This study also found that insecure attachment that children often experienced because of their parents’ alienation towards them usually led to circumstances that culminated in the intensification of the effects of cyberbullying in which they (the children) had been involved. However, those effects were found to affect the female child only (because of her gender). This study concluded that child-parent relationships could influence the level of cyberbullying experience that might affect a particular child. Therefore, this study recommended that stakeholders should collaborate by pulling resources together to develop comprehensive cyberbullying measurement scales suitable for Malaysian society with the primary aim of controlling if not preventing the phenomenon from becoming worse cyber nightmare to the young persons.